Legality of the Use of Armed Forces Against Foreign Parties Obstructing Efforts to Eradicate Illegal, Unregulated, Unreported Fishing in the Exclusive Economic Zone - Hose Pranando, Yuda; Oxana Putra, Erix (Siber International Journal of Advanced Law (SIJAL), 2023)
The purpose of this research is to find out the legality of the entry of Chinese coastguards into Indonesia's EEZ to protect the Kway Fei 10078 Fishing Boat and to find out the legality of using armed forces against foreign parties who obstruct efforts to eradicate Illegal, Unregulated, Unreported Fishing in EEZ and to find out what actions Indonesia should take against China's actions. This study uses normative juridical research methods, namely looking for applicable provisions and library materials. Based on the analysis and research conducted, it was concluded that the entry of the Chinese coastguard into Indonesia's EEZ which protects the Kway Fei 10078 ship is illegal because other countries' ships are only given the right to sail, not protect other ships that violate other countries' EEZ areas according to Article 58 UNCLOS 1982. Retaliation for armed attacks against foreign parties that hinder the eradication of IUU Fishing can be carried out because the right of self-defense is granted by Article 51 of the UN Charter can be realized by a state that is harassed by foreign parties. The actions of disruptive foreign parties are usually in the form of bringing in warships or coastguards to carry out security.